Kemampuan Pemahaman Konsep Siswa Berdasarkan Gender pada Pembelajaran Realistic Mathematics Education Berbantuan Alat Peraga PANDU - Utami, Citra; Anitra, Rien (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
The purpose of this study is to describe the ability to understand mathematical concepts based on gender after participating in Realistic Mathematics Education learning with the props,